American public opinion toward Israel : from consensus to divide - Cavari, Amnon; Freedman, Guy (London : Routledge, 2020)
"This new book examines trends in American public opinion about Israel in over 75 years, from 1944 to 2019. Analyzing data from hundreds of surveys and in jargon-free writing, the authors show that public support for Israel has seen dramatic change toward increased division between partisan and select demographic groups, elaborating on the implications that this important change may have for the countries' special relationship. Scholars and students of American foreign policy, public opinion, Middle East politics, and international relations, as well as policy analysts, policy makers, journalists, and anyone interested in American policy towards Israel will want to read this book"--
Introduction -- Part I: Trends in public support -- Studying American attitudes toward Israel -- Positive affect in American attitudes toward Israel -- Attitudes about the Arab-Israeli conflict and US involvement in the region -- Part 2: Assessing the divide in public support -- Demographic divisions -- Partisan divide -- Affective sources of attitudes -- The nature of the partisan divide over Palestinian independence -- Conclusions.
OCLC-licensed vendor bibliographic record.
Keywords: Israel -- Foreign public opinion, American; United States -- Foreign relations -- Israel; Israel -- Foreign relations -- United States; POLITICAL SCIENCE / General